Gambaran Self Directed Learning Readiness (SDLR) pada Mahasiswa Tingkat Pertama Program Studi Pendidikan Dokter di Fakultas Kedokteran Universitas Sam Ratulangi - Mandolang, Arselina C. (Universitas Sam Ratulangi, 2021)
Abstract: The concept of self-directed learning (SDL) develops rapidly in distance education. This independent learning can be assessed by measuring the score of self-directed learning readiness (SDLR). The Medical Undergraduate Program of Faculty of Medicine Sam Ratulangi University uses the problem based learning (PBL) method which requires students to be able to study independently. The SDLR score of students is very important in the first year of study, therefore, the students will be evaluated by the institution immediately, as well as encouraging them to adapt the independent learning method. This study was aimed to obtain the description of SDLR score in the first-year students of Medical Undergraduate Program of Faculty of Medicine, Sam Ratulangi University. This was a descriptive study with a cross sectional design. The study was conducted on the first year students by using the SDLR questionnaire of Fisher modified by Nyambe. The results showed that a total of 109 students (69.87%) had high SDLR score, 44 students (28.2%) had moderate score, and three students (1.92%) had low score. In conclusion, most of the first year students of Medical Undergraduate Program Faculty of Medicine, Sam Ratulangi University had high SDLR scores.Keywords: self directed learning readiness (SDLR); medical education Abstrak: Konsep belajar mandiri atau self directed learning (SDL) berkembang pesat pada pendidikan jarak jauh. Pembelajaran mandiri ini dapat dinilai dengan mengukur skor self directed learning readiness (SDLR). Program Studi Pendidikan Dokter (PSPD) Fakultas Kedokteran Universitas Sam Ratulangi menggunakan metode problem based learning (PBL) yang menuntut mahasiswa untuk dapat belajar mandiri. Skor SDLR dari mahasiswa sangat penting pada tahun pertama pendidikan agar dapat segera dievaluasi oleh institusi dan untuk mendorong mahasiswa agar dapat menyesuaikan dengan metode belajar mandiri. Penelitian ini bertujuan untuk mengetahui gambaran SDLR pada mahasiswa tingkat pertama Program Studi Pendidikan Dokter (PSPD) di Fakultas Kedokteran Universitas Sam Ratulangi. Jenis penelitian ialah deskritif dengan desain potong lintang. Penelitian ini dilakukan pada mahasiswa tingkat pertama dengan meng-gunakan kuesioner SDLR dari Fisher yang dimodifikasi oleh Nyambe. Hasil penelitian mendapat-kan 109 mahasiswa (69,87%) mempunyai skor SDLR tinggi, 44 mahasiswa (28,2%) dengan skor sedang, dan 3 mahasiswa (1,92%) skor rendah. Simpulan penelitian ini ialah sebagian besar mahasiswa tingkat pertama PSPD Fakultas Kedokteran Universitas Sam Ratulangi mempunyai skor SDLR tinggi.Kata kunci: self directed learning readiness (SDLR); pendidikan kedokteran